Universal screening and decolonization for control of MRSA in nursing homes: follow-up of a cluster randomized controlled trial. Issue 1 (May 2017) - Héquet, D.; Rousson, V.; Blanc, D.S.; Büla, C.; Qalla-Widmer, L.; Masserey, E.; Zanetti, G.; Petignat, C.
Summary: In 2010–11, a trial conducted in nursing homes showed no benefit of meticillin-resistant Staphylococcus aureus (MRSA) universal screening and decolonization over standard precautions to reduce the prevalence of MRSA carriage. Accordingly, no routine screening was performed from 2012. A five-year follow-up shows no new evidence supporting the intervention. Recommendations issued after trial (no screening and decolonization of MRSA residents) were retained.